Toward the inter-channel synergy renaissance in emerging markets: evidence from adding clicks to bricks in Serbia - Stojković, Dragan (2021)
The extent to which businesses in transition economies ensure seamless shopping experience may make the difference between venture’s success or failure. Companies are adhering to this growing market demand by shifting from mono to multiple-channel strategies. In many situations, businesses in transition economies implementing a multiple-channel model trace their beginnings to the pure physical sales model. The newly established intersections between offline and online channels create room for achieving inter channel synergies, thus allowing for omni-channel strategic implementation. This creates the potential to cope with rising market challenges, as well as well-developed international competition. The purpose of this study is to examine which key channel management aspects affect the creation of channel synergy in companies transitioning to omni-channel management. Data collected from 97 businesses in Serbia which switched from brick-and-mortar to brick-and-click model was analysed by SEM-PLS approach. Findings suggest that higher levels of channel synergy are achieved through direct influence of channel support, as well as its indirect effect mediated via offline channel. The study also points out underutilisation of online channel in channel synergy creation, as well as relatively lower implementation of modern inter channel practices in businesses from transition markets.